Introducing directly induced microglia-like (iMG) cells from fresh human monocytes: a novel translational research tool for psychiatric disorders - Ohgidani, Masahiro; Kato, Takahiro A.; Kanba, Shigenobu (Frontiers in Cellular Neuroscience, 2015)
Microglia, glial cells with immunological functions, have been implicated in various neurological diseases and psychiatric disorders in rodent studies, and human postmortem and PET studies. However, the deeper molecular implications of living human microglia have not been clarified. Here, we introduce a novel translational research approach focusing on human microglia. We have recently developed a new technique for creating induced microglia-like (iMG) cells from human peripheral blood. Two cytokines, GM-CSF and IL-34, converted human monocytes into the iMG cells within 14 days, which show various microglial characterizations; expressing markers, forming a ramified morphology, and phagocytic activity with various cytokine releases. We have already confirmed the applicability of this　technique by analyzing iMG cells from a patient of Nasu-Hakola disease (Ohgidani et al., Sci Rep 2014). We herein show possible applications of the iMG cells in translational research. We believe that this iMG technique will open the door to explore various unknown dynamic aspects of human microglia in psychiatric disorders. This also opens new routes for psychopharmacological approach such as drug efficacy screening and personalized medicine.